Effect of malondialdehyde treatment on the IgE binding capacity and conformational structure of shrimp tropomyosin. (15th May 2015) - Song, Yongna; Li, Zhenxing; Lin, Hong; Du, Shuyuan; Hao, Zina; Lin, Haixin; Zhu, Zhen
Highlights: MDA can induce cross-linking of TM. MDA treatment can affect the conformational structure of TM. MDA treatment can decrease the IgE binding capacity of TM. The extent of allergenicity and structure changes relate to the concentration of MDA. Abstract: The aim of this work was to determine the effect of malondialdehyde (MDA) treatment of shrimp tropomyosin (TM) with respect to IgE binding capacity and conformational structure. Following treatment with MDA, changes in TM molecular weight were characterized by SDS–PAGE and TM cross-linking was observed, then the aggregates were recognized by IgG/IgE in immunoblot analysis. Meanwhile, TM allergenicity slowly decreased following MDA treatment. These data show a correlation between the loss of TM structure and allergenic potential. TM secondary structure became more disordered following treatment with increasing concentrations of MDA. Moreover, the enhancement of surface hydrophobicity was also in accordance with the effect caused by MDA. Additionally, MDA treatment resulted in an increase in carbonyl content and a decrease in free amine groups and available lysine. The results suggest that MDA-induced conformational changes in TM can significantly influence the antigenicity and allergenicity of TM.